Risk of eating behavior disorders in adolescents from Cartagena, Colombia - Cogollo, Zuleima; Gómez-Bustamante, Edna Margarita (Investigación y Educación en Enfermería, 2013)
Objective. To estimate the prevalence and explore the relationship of the risk of eating behavior disorders (REDB) with some factors in school-age adolescents from Cartagena, Colombia. Methodology. This was a cross-sectional study, which used probability sampling by conglomerates of high school students (sixth to eleventh grades) in 2012. The REDB was quantified with the SCOFF questionnaire (two or more points). The associations were fitted through a logistic regression model. Results. A total of 2625 students between 10 and 20 years of age (mean = 14 years) participated; 54% were women. A total of 32.5% scored for REDB. The risk factors associated were: problematic consumption of alcohol (OR=1.9; CI95%: 1.4-2.5), female sex (OR=1.6; CI95%: 1.4-1.9), non-heterosexual sexual orientation (OR=1.5; CI95%: 1.1-2.1), consumption of any illegal substance (OR=1.5; CI95%: 1.1-2.1), cigarette smoking at any moment in life (OR=1.5; CI95%: 1.2-1.8), depressive symptoms with clinical importance (OR=1.5; CI95%: 1.2-1.8), and family dysfunction (OR=1.2; CI95%: 1.1-1.5). Conclusion. An important proportion of school-age adolescents from Cartagena presented REDB, which was mainly related to problematic consumption of alcohol and the female sex.